An Intercomparison of Global Reanalysis Products for Southern Africa’s Major Oceanographic Features - Russo, Cristina Serena; Veitch, Jennifer; Carr, Matthew; Fearon, Giles; Whittle, Christo (Frontiers in Marine Science, 2022)
A regional assessment of three global ocean reanalysis products is presented for southern Africa’s major oceanographic features. The reanalyses include Mercator Ocean’s Global Reanalysis (GLORYS), the Commonwealth Scientific and Industrial Research Organisation’s (CSIRO) Bluelink Reanalysis (BRAN) and the Fleet Numerical Meteorology and Oceanography Center’s (FNMOC) global Hybrid Coordinate Ocean Model (HYCOM) reanalysis. The aim is to provide modelers with sufficient information for selecting the appropriate product for use as boundary conditions to force their regional ocean models, as well as to provide marine industries, relevant government agencies and academics with insight into the optimal reanalysis product for their purposes. The reanalyses are compared to both assimilated and independent observational datasets spanning various regions within the southern African marine environment. While all reanalysis products reproduce the eastern and western boundary current systems surrounding southern Africa, limitations exist. BRAN outperforms the other reanalyses in its representation of the Mixed Layer Depth, contributing to its good representation of coastal SSTs in the Benguela upwelling system, whereas GLORYS and HYCOM’s misrepresented MLD result in significant warm biases in this region. The Angola-Benguela Frontal Zone and it’s variability is best reproduced by BRAN and HYCOM. The Agulhas Current system’s major components are well reproduced by both GLORYS and BRAN. HYCOM, however, simulates considerably more early retroflections than are observed which have resulted in its mean eastward location. While all the reanalyses overestimate the occurrence of Agulhas meanders, GLORYS and BRAN resolve the associated variability best. Agulhas Current transport is best resolved by GLORYS, unlike BRAN and HYCOM which largely overestimate the magnitude of its south-westward flow, linked to their misrepresentation of the Current’s vertical structure. The bay-scale and nearshore evaluations highlighted issues pertaining to the resolution of the reanalyses and their use at such a small scale. The reanalyses are limited by their resolution, as well as by their misrepresentation of submesoscale processes or lack thereof, prompting the need for the development of regional downscaled models in and around the southern African oceans based on the global ocean reanalysis products.